2015
DOI: 10.1093/bioinformatics/btu861
|View full text |Cite
|
Sign up to set email alerts
|

scrm: efficiently simulating long sequences using the approximated coalescent with recombination

Abstract: Motivation: Coalescent-based simulation software for genomic sequences allows the efficient in silico generation of short- and medium-sized genetic sequences. However, the simulation of genome-size datasets as produced by next-generation sequencing is currently only possible using fairly crude approximations.Results: We present the sequential coalescent with recombination model (SCRM), a new method that efficiently and accurately approximates the coalescent with recombination, closing the gap between current a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
151
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 9 publications
0
151
0
Order By: Relevance
“…The final model, as shown in Figure 5, was then also simulated using the SCRM simulator 49 , and we verified that Rarecoal was able to infer the true parameters after simulation.…”
Section: Rarecoal Analysismentioning
confidence: 62%
“…The final model, as shown in Figure 5, was then also simulated using the SCRM simulator 49 , and we verified that Rarecoal was able to infer the true parameters after simulation.…”
Section: Rarecoal Analysismentioning
confidence: 62%
“…Neutral simulations were generated with the coalescent simulator scrm (Staab et al 2014) and give a good match to our observed data when plotting derived allele frequency in modern humans against the proportion of derived alleles in the outgroup (Supplemental Fig. S8).…”
Section: Simulationsmentioning
confidence: 99%
“…For each model for IRh, 1-Gb length DNA sequences of 52 individuals were simulated using the coalescent-based algorithm SMC (McVean and Cardin 2005;Marjoram and Wall 2006) implemented in the scrm software package (Staab et al 2015). Similarly, for each model for CRh, 1-Gb length DNA sequences of three individuals were simulated.…”
Section: Comparison Of Demographic Histories and Testing For Fit Agaimentioning
confidence: 99%
“…To investigate our ability to infer recent population size growth/recovery, we simulated 200 DNA sequence samples using the scrm software package (Staab et al 2015). The stairway plot estimation based on 75 high-coverage IRh is assumed to be the true demographic model.…”
Section: Simulation Study Assuming a Population Size Recoverymentioning
confidence: 99%